Spatial and temporal distribution of phytoplankton with emphasis on the harmful and toxic algae in the Limboto Lake - Miftahul Khair Kadim; Femy M. Sahami; Dewi J. Hasiru (Tomini Journal of Aquatic Science, 2020)
This study aims to describe Limboto Lake's condition based on the spatial-temporal abundance of phytoplankton and the presence of harmful algae species. Sampling was conducted in February, March, and April 2018 at six stations. The phytoplankton found in Limboto Lake consisted of 7 divisions from 80 species, namely Chlorophyta (35 species), Euglenophyta (17 species), Bacillarophyta (13 species), Cyanophyta (7 species), Cryptophyta (4 species), Dinophyta (3 species) and Chyrosphyta (1 species). The results of the phytoplankton distribution analysis in Limboto Lake varied on average among stations as well as observation times. The results show that the average of phytoplankton abundance at stations 1, stations 2, stations 3, and stations 4 categorized as medium polluted waters with 4,903 ind/L, 5,000 ind/ L, 9,418 ind/L, and 10,049 ind/L, respectively. The abundance at station five is included in the lightly polluted category with an average phytoplankton abundance of 1,541 ind/L, while station 6 is in the heavily polluted category with the average value of 20,894 ind/L. Species that can be used as indicator species for pollution are those with the highest abundance value, namely Microcystis sp., which indicates that Limboto Lake contains high nitrate and phosphate.